Relação entre o verbal e o visual: leitura de uma gravura de Dürer, feita por Saramago (Significação: Journal of Audiovisual Culture, 2003)
The central purpose of this text consists in, by using some central concepts of theoretical semiotic perspective of the School of Paris, developing an analysis of the reading that the narrator of the text The gospel according to Jesus Christ, by José Saramago, does of a picture produced by Dürer. The basic hypothesis of this work is that the description of the mentioned picture done by the narrator refers, metonymically, to the romance structure as a whole.